The art of genes : how organisms make themselves - Coen, Enrico (Oxford University Press, 1999)
Coen's book is spiced with historic quotations and examples of plants' and animals' intriguing behaviour contains a wealth of interesting material Coen communicates his immense learning with a hundred appealing tales'Max PerutzHow is a tiny fertilised egg able to turn itself into a human being? How can an acorn transform itself into an oak tree? Over the past twenty years there has been a revolution in biology. For the first time we have begun to understand how organisms make themselves. The Art of Genes gives an account of these new and exciting findings, and of their broader significance for.